Antigone - Sophocles (Methuen Drama, 2012)
The story of one sister's loyalty to both her brothers, regardless of their acts or opposing political beliefs, 'Antigone' is one of the most consistently popular plays in the history of drama. This translation, by Don Taylor, was commissioned by the BBC, and was first broadcast in autumn, 1986.
10.5040/9781408173268.00000004
Keywords: Drama; Antigone (Greek mythology)